Genomic sequencing in a cohort of individuals with fibular aplasia, tibial campomelia, and oligosyndactyly (FATCO) syndrome. Issue 4 (6th January 2023) - Matalon, Dena R.; Bhoj, Elizabeth J.; Li, Dong; McDougall, Carey; Schindewolf, Erica; Khalek, Nahla; Wilkens, Alisha; McManus, Morgan; Deardorff, Matthew A.; Zackai, Elaine H.
Abstract: Fibular aplasia, tibial campomelia, and oligosyndactyly (FATCO) syndrome (MIM 246570) is a rare disorder characterized by specific skeletal findings (fibular aplasia, shortened or bowed tibia, and oligosyndactyly of the foot and/or hand). Typically, no other anomalies, craniofacial dysmorphism, or developmental delays are associated. Here we report three unrelated individuals with limb anomalies consistent with FATCO syndrome who have been followed clinically for 5 years. Genetic testing of previously reported individuals with FATCO syndrome has not revealed a genetic diagnosis. However, no broader sequencing approaches have been reported. We describe the results of the three individuals with FATCO syndrome from exome and genome sequencing, all of which was nondiagnostic. Our study suggests that FATCO syndrome is not the result of a simple monogenic etiology.